2018
DOI: 10.21873/cgp.20074
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Immunoprecipitation and DNA Sequencing Identified a LIMS1/ILK Pathway Regulated by LMO1 in Neuroblastoma

Abstract: The downstream of LMO1-regulatory cascade includes a tumor-promoting LIMS1/ILK pathway, which has a potential to be a novel therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…RNA sequencing (RNA-seq) and gene set enrichment analysis (GSEA) indicated that matrisome, extracellular matrix-associated proteins, integrins coding signature genes were enriched in the neuroblastoma cell lines expression high levels of LMO1. Later on, a mechanistic study using chromatin immunoprecipiation and DNA sequencing demonstrated that in neuroblastoma, LMO1 could affect LIMSI ( LIM and senescent cell antigen-like domains 1 ), Ras suppressor protein 1 ( RSU1 ), and relaxin 2 ( RLN2 ) gene, and regulate a carcinogenic LIMSI/integin-linked kinase pathway ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing (RNA-seq) and gene set enrichment analysis (GSEA) indicated that matrisome, extracellular matrix-associated proteins, integrins coding signature genes were enriched in the neuroblastoma cell lines expression high levels of LMO1. Later on, a mechanistic study using chromatin immunoprecipiation and DNA sequencing demonstrated that in neuroblastoma, LMO1 could affect LIMSI ( LIM and senescent cell antigen-like domains 1 ), Ras suppressor protein 1 ( RSU1 ), and relaxin 2 ( RLN2 ) gene, and regulate a carcinogenic LIMSI/integin-linked kinase pathway ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that miR-450b-3p was downregulated in breast cancer and could inhibit HER3 expression through the PI3K/Akt pathway (31). LIM domain only 1 (LMO1), which as a hsa_circ_0021087 host gene, has been reported as an oncogene in multiple tumors, such as lung cancer (32), neuroblastoma (33) and gastric cancer (34). Pathway analysis revealed that it is also involved in several cancer-associated pathways, such as cell cycle, viral carcinogenesis and pathways in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ChIP-seq analysis demonstrated the direct association of LMO1 protein with these three genes in two neuroblastoma cell lines SK-N-SH and LAN-5. [73] The authors further showed that knocking down LMO1 expression suppressed the expression of the three genes. [73] In subsequent studies conducted by the same research group, it was found that LMO1 indirectly downregulates 18 tumor-suppressive microRNAs in SK-N-SH cells, including hsa-miR-34a-5p and 7 members of the let-7 family, [74] suggesting that downregulating the expression of those miRNAs is one of the mechanisms underlying the oncogenic function of LMO1.…”
Section: The Oncogenic Mechanism Of Lmo1 In Neuroblastomamentioning
confidence: 99%
“…[57] Additional downstream genes of LMO1 have been identified. Saeki et al [73] identified three genes directly regulated by LMO1 at the transcriptional level. These three genes are LIM and senescent cell antigen-like domains 1 (LIMS1), Ras suppressor protein 1 (RSU1), and relaxin 2 (RLN2).…”
Section: The Oncogenic Mechanism Of Lmo1 In Neuroblastomamentioning
confidence: 99%